Monitoring policy and actions on food environments: rationale and outline of the INFORMAS policy engagement and communication strategies. (17th September 2013) - Brinsden, H.; Lobstein, T.; Landon, J.; Kraak, V.; Sacks, G.; Kumanyika, S.; Swinburn, B.; Barquera, S.; Friel, S.; Hawkes, C.; Kelly, B.; L'Abbé, M.; et al.
Summary: The International Network for Food and Obesity/non‐communicable diseases Research, Monitoring and Action Support (INFORMAS) proposes to collect performance indicators on food policies, actions and environments related to obesity and non‐communicable diseases. This paper reviews existing communications strategies used for performance indicators and proposes the approach to be taken for INFORMAS. Twenty‐seven scoring and rating tools were identified in various fields of public health including alcohol, tobacco, physical activity, infant feeding and food environments. These were compared based on the types of indicators used and how they were quantified, scoring methods, presentation and the communication and reporting strategies used. There are several implications of these analyses for INFORMAS: the ratings/benchmarking approach is very commonly used, presumably because it is an effective way to communicate progress and stimulate action, although this has not been formally evaluated; the tools used must be trustworthy, pragmatic and policy‐relevant; multiple channels of communication will be needed; communications need to be tailored and targeted to decision‐makers; data and methods should be freely accessible. The proposed communications strategy for INFORMAS has been built around these lessons to ensure that INFORMAS's outputs have the greatest chance of being used to improve food environments.